Estudio de prefactibilidad para la instalación de una planta productora y exportadora de arándanos (Vaccinium myrtillus) orgánicos - Cavero Valverde, Marco Antonio (2020)
The Company will be settled in the department of Ica and will have a capacity of 428,4 tons of blueberries per year. The demand for the project’s final year will be 342 tons and each kilogram will be sold at a price of US$ 12,48. The production process for the blueberry filled clamshells consists of the harvesting, calibration, inspection, and packaging of the blueberries. The factory where the production and administration areas will be located will count with 1.655 square meters and the total land of the company will be 50 acres considering the blueberry fields. The investment needed to execute the project is S / 9 350 731, 80% which will be financed by a bank and the remaining 20% by own capital. The economic flow of the project reflects an Internal Rate of Return (IRR) of 40% and a recovery period of 3,23 years.